Investigating the relationship between organizational culture and human resource productivity (case study of government department employees in Ilam province) - Jafari, Mohammad Bagher (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2021)
Background and purpose: Organizational culture and human resource productivity are among the categories that have attracted the attention of many behavioral science and management experts in recent years. The current research aimed to investigate the relationship between organizational culture and human resource productivity among government department employees in Ilam province. Methodology: The research is correlational and descriptive, and its population consists of all the education workers of Ilam province; 164 employees were selected as a sample through Cochran’s sampling formula. To collect data, a standard questionnaire including general questions about the status of the respondents and specialized questions about organizational culture and human resource productivity in education and training was used in the form of questions with a Likert scale, and Cronbach’s alpha method was used to check its reliability. In data analysis, descriptive statistics and inferential statistics methods such as t-test, analysis of variance tests with a significance level of 05%, and Pearson’s correlation coefficient were used to correlate variables using SPSS software. Results: The findings of the research that took place in education in Ilam province indicate a significant and direct relationship between organizational culture and human resource productivity, and culture directly impacts the organization’s performance and effectiveness. Conclusion: The results showed a direct and meaningful relationship between the existence of close and intimate relationships between human resources and the organization’s productivity.